Agro-meteorological services in the era of climate change: a bibliometric review of research trends, knowledge gaps, and global collaboration - Khatibu, Salma; Ngowi, Edwin (Frontiers in Climate, 2025)
IntroductionAgro-meteorological services are crucial for mitigating climate variability’s impact on agriculture and enhancing food security. Despite their importance, the global research landscape in this field remains underexplored. This study examines the evolution of agro meteorological research from 2010 to 2024, focusing on trends, contributors, and regional developments.MethodsA bibliometric analysis was conducted using the Dimensions database, with visualizations created via VOSviewer. The study analyzed publication trends, key institutions, authors, journals, and subject clusters. Statistical correlations assessed collaboration and institutional impact.ResultsThe results revealed that publications increased steadily, peaking in 2020 (r = 0.92, p < 0.01), reflecting emphasis on sustainability and climate adaptation. Collaborative publications correlated strongly with institutional impact (r = 0.75, p < 0.01), led by Wageningen University and the University of Chinese Academy of Sciences. Sustainability and The Science of the Total Environment were key journals. Sub- Saharan Africa and South Asia showed significant research growth (r = 0.85, p < 0.01).DiscussionThe results highlight the field’s global, interdisciplinary scope and rising contributions from developing regions. However, capacity gaps and limited integration of indigenous knowledge persist. Inclusive partnerships and capacity building are essential to strengthen agro meteorological services and address climate challenges effectively.